2016
DOI: 10.1136/archdischild-2015-310121
|View full text |Cite
|
Sign up to set email alerts
|

Toxic shock syndrome in Australian children

Abstract: This study highlights the importance of early recognition of TSS and supports rapid tertiary referral and intensive care management, which includes the use of adjunctive therapy with intravenous immunoglobulin and clindamycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 21 publications
5
33
0
1
Order By: Relevance
“…Str-TSS cases had a more severe prognosis than the Sta-TSS cases, including longer PICU stay, higher PIM2 scores, higher number of organ failure with more frequent acute respiratory distress syndrome, and required mechanical ventilation more often and for a longer time, in accordance to UK and Australian studies ( 5 , 6 , 40 ). Although not significant, the case-fatality rate for Str-TSS (20%) was higher than Sta-TSS (7%), that is consistent with the meta-analysis of Chuang et al, who analyzed 27 and 30 studies focused on Sta- and Str-TSS, respectively.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Str-TSS cases had a more severe prognosis than the Sta-TSS cases, including longer PICU stay, higher PIM2 scores, higher number of organ failure with more frequent acute respiratory distress syndrome, and required mechanical ventilation more often and for a longer time, in accordance to UK and Australian studies ( 5 , 6 , 40 ). Although not significant, the case-fatality rate for Str-TSS (20%) was higher than Sta-TSS (7%), that is consistent with the meta-analysis of Chuang et al, who analyzed 27 and 30 studies focused on Sta- and Str-TSS, respectively.…”
Section: Discussionsupporting
confidence: 80%
“…Toxic Shock Syndrome (TSS) is a severe acute illness characterized by high fever, hypotension, rash, multi-organ system dysfunction, and desquamation during convalescence. TSS is caused by toxin-producing strains of Staphylococcus aureus or Streptococcus pyogenes and occurs in both adult and pediatric patients ( 1 5 ). TSS remains a rare but severe disease, with a mortality rate that varies from 4 to 27% for streptococcal (Str) TSS ( 2 4 ) and from 0 to 22% for menstrual and non-menstrual staphylococcal (Sta) TSS ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to underline that unlike other streptococcal invasive infections that can lead to shock, SSTS is due to toxins that act as superantigens triggering an uncontrolled inflammatory response causing endothelial lesion and evolving to shock with multiple organ failure. 6,7 Thus, treatment with clindamycin leads to better survival in cases of STSS, due to the antitoxin effect of clindamycin compared with B-lactam agents, so its use is recommended 11 ; in this sample, it was administered in more than half of the cases. Although all the patients in our study made a good recovery, the death rate in the literature has been shown to be as high as 28%.…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines act on the capillary endothelium, increase its permeability, and eventually lead to shock, manifesting with hypotension, fever, rash, and multiple organ failure. 6,7 Children usually have a weak antibody response against the toxins that cause the syndrome. 8 The diagnosis of STSS often involves the recognition by the clinician of a constellation of signs and symptoms not always easy to identify, as well as the microbiological determination of S. pyogenes.…”
Section: Introductionmentioning
confidence: 99%
“…The production of enterotoxin was previously assessed using toxin detection kits (Denka Seiken Co. Ltd, Tokyo, Japan) for TSST-l and staphylococcal enterotoxins A-D (SEA-SED). In addition, TSST-l production was evaluated using an isoelectric focusing procedure [9, 10]. Bacteria were cultured on blood agar for 24 h, then reincubated on blood agar for another 24 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%